Case Report: A very rare case of diffuse large B-cell lymphoma with cardiac and ovarian involvement - Du, Yadan; Tian, Yuting; Chen, Yawen; Cheng, Shuaihua; Gao, Jianping (Frontiers in Oncology, 2025)
BackgroundDiffuse large B-cell lymphoma (DLBCL) is the most prevalent type of aggressive lymphoma, commonly spreading to sites such as the lymph nodes, spleen, bone marrow, liver, lungs, and central nervous system. However, metastasis to the heart and ovaries is relatively uncommon.Case DescriptionA 63-year-old woman visited the hospital with abdominal pain and bloating, but showed none of the typical signs of lymphoma. Imaging scans revealed abnormal masses in both the pericardium and ovaries. A biopsy confirmed it was DLBCL, presenting in the rare form of simultaneous spread to the heart lining and ovaries. During the course of illness, she also developed atrial arrhythmia. Doctors adopted a phased treatment approach: four cycles of R-CEOD chemotherapy led to a noticeable reduction in the heart tumor and improvement in her heart rhythm. This was followed by four cycles of R-CHOP, which further shrank the cardiac lesion and cleared the abdominal tumors completely. The treatment was well tolerated, and at a three-month follow-up, there was no sign of recurrence. Her heart function remained stable, with a left ventricular ejection fraction (LVEF) of 60%.ConclusionThis case highlights the importance of early detection of atypical metastases in DLBCL through a combination of various imaging and pathological tests. Additionally, personalized treatment strategies may contribute to better patient outcomes.